1, 8‐Diazabicyclo[5.4.0]undec‐7‐ene‐Catalyzed Carbonylative Cyclization of Propargylic Alcohols with Elemental Sulfur. Issue 10 (14th March 2018) - Hu, Yuya; Yin, Zhiping; Werner, Thomas; Spannenberg, Anke; Wu, Xiao‐Feng
Abstract : A carbonylation procedure involving the cyclization of propargylic alcohols with elemental sulfur was developed. With 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene as the catalyst, elemental sulfur and carbon monoxide are activated and incorporated into propargylic alcohols. Good to excellent yields of the desired sulfur‐containing heterocycles were obtained at room temperature. Abstract : A carbonylation procedure involving the cyclization of propargylic alcohols with elemental sulfur is developed. With 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) as the catalyst, elemental sulfur and carbon monoxide can be activated and incorporated into propargylic alcohols. Good to excellent yields of the desired 1, 3‐oxathiolan‐2‐ones are obtained at room temperature.